Over the Draft Pages of Marina Tsvetaeva - GEVORGYAN, TATYANA (Bulletin of Yerevan University H: Russian Philology, 2021)
Ariadna Efron, daughter of the poetess Marina Tsvetaeva, has made an invaluable con-tribution in preserving and publishing Tsvetaeva’s heritage, interpreting her handwritten copies, various drafts and notes. The article estimates the work done by Efron and puts into scientific circulation for the first time some archival materials which shed light on the nuances of Tsvetaeva’s creative laboratory.
Keywords: archive, interpretation, Efron, “Garden”, “Poem of the Air”